Professionalism and Literacy: Pillars of Work Readiness for Accounting Careers in the Modern Era - Meikhati, Ety (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
The digital transformation era has significantly reshaped the competencies required for workforce entry, particularly accounting. This study empirically examines the influence of professionalism, measured by accounting competency certification, and literacy, measured by digital and human literacy, on career readiness in accounting. A quantitative research design was employed, involving 97 accounting graduates from various universities in the Surakarta Residency area, selected using purposive sampling. The results indicate that accounting competency certification, digital literacy, and human literacy each significantly and positively affect accounting career readiness. Among these factors, human literacy exhibits the most substantial influence, underscoring the importance of critical thinking, emotional intelligence, empathy, collaboration, and ethical decision-making in preparing individuals' career readiness.